La mobilisation religieuse islamique durant la guerre d’indépendance turque - Faruk Bilici (Cahiers Balkaniques)
Abstract: The contribution of religion in the conceptual sense of the term as well as religious currents to the Turkish independence movement is one of the dimensions on which published works are too often speculative. Whatever the future intentions of Mustafa Kemal and his companions against the sultanate, the caliphate and Islam, it is undeniable that the religious – let us say, Islamic, mainly Sunni, and to a lesser extent Jewish – played a primordial role in mobilizing the population against the occupying powers. The cooperation between ulemas, brotherhoods, military and notables represented a certain strategic success, insofar as the official objective was to save the sultan-caliph prisoner of the “infidels” and the Muslim people. Also, in the congresses of resistance organized throughout the different provinces (Thrace, Izmir, Erzurum, Sivas), and even in the Grand National Assembly, the representation of regular and secular clergy is very important. However, this same cleric, in the person of the sultan-caliph, the head of the religious body (the "şeyh’ül-Islam"), and some religious press organs tries to oppose this movement, using its institutions, such as the fatwa.